Atom Transfer Radical Copolymerization of Phenoxycarbonylmethyl Methacrylate with Methylmethacrylate: Their Monomer Reactivity Ratios and Thermal Stabilities - Cankaya, Nevin; Demirelli, Kadir (Chem Soc Pakistan, 2011)
The atom transfer radical polymerization of phenoxycarbonylmethyl methacrylate (PCMMA) and its atom transfer radical copolymerization (ATRP) with methyl methacrylate (MMA) were performed in bulk at 110 degrees C in the presence of ethyl 2-bromoacetate, cuprous(I) bromide (CuBr), and 2,2'-bipyridine. Also, free-radical polymerization of PCMMA was carried out in the presence of 2,2'-azobisisobutyronitrile in 1,4-dioxane solvent at 60 degrees C. The structure of homo and copolymers was characterized by IR, H-1 and C-13 NMR techniques. The composition of the copolymers was calculated from H-1-NMR spectra. The in situ addition of ethylmethacrylate to a macroinitiator of poly(phenoxycarbonylmethyl methacrylate) [Mn=32700, PD=1.53] afforded an AB-type block copolymer. The molecular weight and molecular weight distribution were obtained by Gel Permeation Chromatography (GPC). The polydispersity for the living copolymer (65% PCMMA units by mole) was 1.66. For copolymerization system, their monomer reactivity ratios were obtained by using both Kelen-Tudos and Fineman-Ross equations. The initial decomposition temperatures of the resulting copolymers decreased with increasing mole fraction of PCMMA in them which indicates that heat resistance of copolymer have been improved by decreasing MMA units. The dielectric parameters of the homo-and copolymer were calculated at 1 KHz at different temperature. An increase in the dielectric constant is observed due to interfacial polarization.
Keywords: Methyl-Methacrylate; Graft-Copolymers; Polymerization; Acrylate; Halides; Complexes; Catalyst; Styrene